Burke, Kant and Lyotard: reflections on the sublime (Palíndromo, 2014)
The theme of the sublime has been developed by scholars since the eigh- teenth century in an attempt to find an artistic theory about this aesthetic catego- ry. In 1757, Edmund Burke wrote A philo- sophical inquiry into the origin of our ideas of the sublime and the beautiful; in 1790, Immanuel Kant published  the  Critique of Judgment Faculty; and in 1982, Jean- François Lyotard reactivated the theme with the production of The sublime and the avant-garde (among other writings that he would launch later). This article aims to present the concepts and discussions ex- pressed by these three authors about the beautiful and especially the sublime, as Kant was influenced by the aesthetic ideas of Burke and Lyotard uses the two previ- ous definitions to formulate a new idea of sublime that justifies the avant-garde arts. To the basement, in addition to the cited authors, were used studies such as José Thomaz Brum, Wilson Coutinho, Rodrigo Duarte, Valerio Rohden, Marcia Tiburi, and others.
Keywords: communication; philosophy; aesthetics; beautiful; sublime